2021
DOI: 10.1371/journal.ppat.1009287
|View full text |Cite
|
Sign up to set email alerts
|

Baseline T cell immune phenotypes predict virologic and disease control upon SARS-CoV infection in Collaborative Cross mice

Abstract: The COVID-19 pandemic has revealed that infection with SARS-CoV-2 can result in a wide range of clinical outcomes in humans. An incomplete understanding of immune correlates of protection represents a major barrier to the design of vaccines and therapeutic approaches to prevent infection or limit disease. This deficit is largely due to the lack of prospectively collected, pre-infection samples from indiviuals that go on to become infected with SARS-CoV-2. Here, we utilized data from genetically diverse Collabo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
(71 reference statements)
2
24
0
Order By: Relevance
“…It has been long argued whether death resulting from dysregulation of inflammation in sepsis is due to a poor initial immune response followed by high pathogen burden and secondary hyper-inflammation or, alternatively, is due to a disproportionately strong initial immune response against a low pathogen burden that leads to inadequate systemic responses. Our findings argue for the former, in line with studies of bacterial sepsis 41 and respiratory infections [42][43][44] , and consistent with the efficacy of approaches that boost the baseline/early resistance such as vaccines 45,46 .…”
Section: Discussionsupporting
confidence: 88%
“…It has been long argued whether death resulting from dysregulation of inflammation in sepsis is due to a poor initial immune response followed by high pathogen burden and secondary hyper-inflammation or, alternatively, is due to a disproportionately strong initial immune response against a low pathogen burden that leads to inadequate systemic responses. Our findings argue for the former, in line with studies of bacterial sepsis 41 and respiratory infections [42][43][44] , and consistent with the efficacy of approaches that boost the baseline/early resistance such as vaccines 45,46 .…”
Section: Discussionsupporting
confidence: 88%
“…Such interrogation may provide insights into the development of adaptive NK cells in humans with a much broader range of genetic variability, relative to inbred mice. These investigations should incorporate numeric assessment of NK cells across tissues and may be further extended through the breeding of F 1 mice with either strains of interest or some of the classical inbred strains, as has been previously investigated (25). These analyses may elucidate the molecular underpinnings for variation in the baseline differences in NK cell number and expression of NK cell receptors such as Ly49H.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional studies are required to determine whether T reg -modulating therapies could be of benefit in limiting COVID-19 severity. We recently demonstrated that in a mouse model of SARS-CoV, an elevated steady-state, preinfection frequency of T regs correlates with protection from high viral loads and disease upon infection ( 70 ), thereby contributing to the notion that T regs could play a protective role in limiting disease. However, examination of prospectively collected pre–COVID-19 pandemic samples from humans that went on to become infected would be required to establish whether T reg abundance is predictive of viral loads or disease severity upon SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%